A comparative study of wavelength-dependent photoinactivation in photosystem II of drought-tolerant photosynthetic organisms in Antarctica and the potential risks of photoinhibition in the habitat. (23rd July 2018) - Kosugi, Makiko; Maruo, Fumino; Inoue, Takeshi; Kurosawa, Norio; Kawamata, Akinori; Koike, Hiroyuki; Kamei, Yasuhiro; Kudoh, Sakae; Imura, Satoshi
Abstract: Background and Aims: All photosynthetic organisms are faced with photoinhibition, which would lead to death in severe environments. Because light quality and light intensity fluctuate dynamically in natural microenvironments, quantitative and qualitative analysis of photoinhibition is important to clarify how this environmental pressure has impacted ecological behaviour in different organisms. Methods: We evaluated the wavelength dependency of photoinactivation to photosystem II (PSII) of Prasiola crispa (green alga), Umbilicaria decussata (lichen) and Ceratodon purpureus (bryophyte) harvested from East Antarctica. For evaluation, we calculated reaction coefficients, E pi s, of PSII photoinactivation against energy dose using a large spectrograph. Daily fluctuation of the rate coefficient of photoinactivation, k pi, was estimated from E pi s and ambient light spectra measured during the summer season. Key Results: Wavelength dependency of PSII photoinactivation was different for the three species, although they form colonies in close proximity to each other in Antarctica. The lichen exhibited substantial resistance to photoinactivation at all wavelengths, while the bryophyte showed sensitivity only to UV-B light (<325 nm). On the other hand, the green alga, P. crispa, showed ten times higher E pi to UV-B light than the bryophyte. It was much more sensitive to UV-A (325–400 nm). The risk of photoinhibition fluctuated considerably throughout the day. On the other hand, E pi s were reduced dramatically for dehydrated compared with hydrated P. crispa . Conclusions: The deduced rate coefficients of photoinactivation under ambient sunlight suggested that P. crispa needs to pay a greater cost to recover from photodamage than the lichen or the bryophyte in order to keep sufficient photosynthetic activity under the Antarctic habitat. A newly identified drought-induced protection mechanism appears to operate in P. crispa, and it plays a critical role in preventing the oxygen-evolving complex from photoinactivation when the repair cycle is inhibited by dehydration.